A review on functional nanoarchitectonics nanocomposites based on octahedral metal atom clusters (Nb6, Mo6, Ta6, W6, Re6): inorganic 0D and 2D powders and films. Issue 1 (31st December 2022) - Nguyen, Ngan T. K.; Lebastard, Clément; Wilmet, Maxence; Dumait, Noée; Renaud, Adèle; Cordier, Stéphane; Ohashi, Naoki; Uchikoshi, Tetsuo; Grasset, Fabien
ABSTRACT: This review is dedicated to various functional nanoarchitectonic nanocomposites based on molecular octahedral metal atom clusters (Nb6, Mo6, Ta6, W6, Re6 ). Powder and film nanocomposites with two-dimensional, one-dimensional and zero-dimensional morphologies are presented, as well as film matrices from organic polymers to inorganic layered oxides. The high potential and synergetic effects of these nanocomposites for biotechnology applications, photovoltaic, solar control, catalytic, photonic and sensor applications are demonstrated. This review also provides a basic level of understanding how nanocomposites are characterized and processed using different techniques and methods. The main objective of this review would be to provide guiding significance for the design of new high-performance nanocomposites based on transition metal atom clusters. GRAPHICAL ABSTRACT: uf0001